'Test Now, Stop HIV': COVID-19 and the idealisation of quarantine as the 'end of HIV'. Issue 11 (1st November 2021) - Ledin, Chase; Weil, Benjamin
Abstract: The emergence of COVID-19 precipitated varied responses from public health officials in London, England. In April 2020, clinicians at 56 Dean Street sexual health and advice clinic in central London described social isolation as 'a unique window of opportunity' to 'break the chain' in HIV transmission. This was followed by critical responses within HIV prevention circles. Drawing from these responses, this article examines the implications of the clinic's 'Test Now, Stop HIV' campaign by asking how has the early COVID-19 pandemic reshaped institutional responses and strategies to end HIV transmission in England? We assess how campaign messages developed between April and May 2020. We analyse materials related to the campaign, including the clinic's Twitter account, the campaign website, and journalism in mainstream media. Based on this information, we discuss three themes: testing and issues of access; the biopolitics of testing; and the idealism of quarantine. We draw on sociology, cultural theory and science and technology studies to describe how the 'end of HIV' was constructed through the link between COVID-19 and HIV. We suggest the campaign reinscribes historical perceptions of abstinence and quarantine as idealised HIV prevention strategies, and thus fails to address safer sex in the time of Coronavirus.